The role of age of acquisition and language usage in early, high-proficient bilinguals: An fMRI study during verbal fluency - Perani, Daniela; Abutalebi, Jubin; Paulesu, Eraldo; Brambati, Simona; Scifo, Paola; Cappa, Stefano F.; Fazio, Ferruccio (Human brain mapping, 2003)
We assessed the effects of age of acquisition and language exposure on the cerebral correlates of lexical retrieval in high‐proficient, early‐acquisition bilinguals. Functional MRI was used to study Spanish–Catalan bilinguals who acquired either Spanish or Catalan as a first language in the first years of life. Subjects were exposed to the second language at 3 years of age, and have used both languages in daily life since then. Subjects had a comparable level of proficiency in the comprehension of both languages. Lexical retrieval with the verbal fluency task resulted in the well‐established pattern of left hemispheric activation centered on the inferior frontal region. The effect of age of acquisition was assessed by dividing the subjects into two groups, on the basis of the language acquired first (Catalan‐born or Spanish‐born bilinguals). Functional comparisons indicated that less extensive brain activation was associated with lexical retrieval in the language acquired earlier in life. The two groups were also different in language usage/exposure, as assessed with a specific questionnaire; in particular, the exposure to the second language (Spanish) was less intensive in the case of Catalans. This was reflected in a significant interaction, indicating a more extensive activation in Catalans during production in Spanish. Overall, these results indicate that, during a production task, both age of acquisition and language exposure affect the pattern of brain activation in bilinguals, even if both languages are acquired early and with a comparable level of proficiency. Hum. Brain Mapping 19:170–182, 2003. © 2003 Wiley‐Liss, Inc.